2013
DOI: 10.1098/rspb.2013.1082
|View full text |Cite
|
Sign up to set email alerts
|

The extraembryonic serosa protects the insect egg against desiccation

Abstract: Insects have been extraordinarily successful in occupying terrestrial habitats, in contrast to their mostly aquatic sister group, the crustaceans. This success is typically attributed to adult traits such as flight, whereas little attention has been paid to adaptation of the egg. An evolutionary novelty of insect eggs is the serosa, an extraembryonic membrane that enfolds the embryo and secretes a cuticle. To experimentally test the protective function of the serosa, we exploit an exceptional possibility to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 48 publications
5
117
0
Order By: Relevance
“…8D-F, schematic). While the amnion then extends with the embryo, the serosa remains largely static under the eggshell, to which it becomes attached through its secreted cuticle (Hilbrant et al, 2016;Jacobs et al, 2013). After Tc-Doc RNAi, serosal window closure often does not occur ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8D-F, schematic). While the amnion then extends with the embryo, the serosa remains largely static under the eggshell, to which it becomes attached through its secreted cuticle (Hilbrant et al, 2016;Jacobs et al, 2013). After Tc-Doc RNAi, serosal window closure often does not occur ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to first provide protection to the embryo in the form of desiccation resistance (Goltsev et al, 2009;Jacobs et al, 2013;Vargas et al, 2014) and defense against pathogens (Jacobs et al, 2014), and later to leave the embryo uncovered, they perform a wide array of morphogenetic rearrangements. The degree to which EE reorganization affects the embryo ranges from small-scale effects on germ band extension and retraction in Drosophila (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In N. vespilloides , egg size might function primarily to confer resistance to desiccation (Jacobs et al. 2013). Casual observation suggests that humidity levels in our laboratory breeding boxes are generally high, whether or not parents provide postnatal care.…”
Section: Discussionmentioning
confidence: 99%
“…25 Recent experiments suggest that the extra-embryonic serosa is an evolutionary novelty of insect eggs to protect them against desiccation. 34 But does it play an active role during early embryonic morphogenesis? While it is still an open question whether initiation of serosa expansion is an active process or merely a consequence of tensile forces exerted by the contracting embryonic rudiment, our Tribolium imaging studies suggested that the serosa is needed during the later stages of epithelial rearrangement.…”
Section: A Qualitative Model For Cell and Tissue Dynamics Driving Epimentioning
confidence: 99%